2017
DOI: 10.3892/mco.2017.1345
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative safety analysis of transcatheter arterial chemoembolization for hepatocellular carcinoma patients with preprocedural leukopenia or thrombocytopenia

Abstract: Abstract.Patients with hepatocellular carcinoma (HCC) exhibit a high incidence of concomitant cirrhosis with leukopenia and/or thrombocytopenia. In the present study, perioperative changes in the white blood cell (WBC) and platelet (PLT) counts and associated complications were investigated to assess the safety of transcatheter arterial chemoembolization (TACE) for HCC patients with preprocedural leukopenia or thrombocytopenia. The records of 1,461 HCC patients who received TACE between January 2012 and Decemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…In a retrospective study of more than 2,000 TACEs, the highest reported bleeding rate, which occurred in 2.2% of the procedures, involved the vascular access site and was due to inappropriate local hemostasis. 85…”
Section: Transarterial Chemoembolizationmentioning
confidence: 99%
“…In a retrospective study of more than 2,000 TACEs, the highest reported bleeding rate, which occurred in 2.2% of the procedures, involved the vascular access site and was due to inappropriate local hemostasis. 85…”
Section: Transarterial Chemoembolizationmentioning
confidence: 99%
“…Three studies found that platelet counts < 10 Â 10 9 /L were associated with an increased risk of bleeding, 124,127,130 whereas the remaining eight studies demonstrated no association between platelet counts and bleeding. This could be explained by higher cutoffs for thrombocytopenia (50 Â 10 9 /L) 132,134 as well as higher median platelet counts 128,131 in the latter studies. Furthermore, a large proportion of studies on solid tumors focused on bleeding related to invasive procedures.…”
Section: Discussionmentioning
confidence: 73%
“…Thus, 52 studies were included for quality assessment and data extraction. 2, Studies included patients with hematological malignancy (n ¼ 31), 2,94-123 solid tumors (n ¼ 11), [124][125][126][127][128][129][130][131][132][133][134] or both (n ¼ 10). [135][136][137][138][139][140][141][142][143][144] There were 3 posthoc studies on data from randomized controlled trials, 104,117,120 2 case series 111,112 and 47 cohort studies, among which data were collected prospectively in 24 96,97,99,105-110,113,115,116,118,123,126,127 129-131,135,136,140,142,144 and obtained from medical records in 23.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies report a decrease in platelet count after TACE 48 , 49 . In contrast, we observed no significant decrease in the platelet count in our patients.…”
Section: Discussionmentioning
confidence: 99%